Measuring the production efficiency of alternative land tenure contracts in a mixed crop-livestock system in Ethiopia - Gavian, S.; Ehui, Simeon K. (International Livestock Research Institute, 2002)
Although the question of relative production efficiency of indigenous land rights is central to a discussion of land reform in sub-Saharan Africa, there is relatively little rigorous empirical research because of a lack of adequate disaggregated data with the exception of few studies, the subject has not benefited from rigorous empirical analysis. Further, most studies have covered only areas of rainfed agriculture. This chapter determines the relative production efficiency of alternative land tenure arrangements and the sources of differences in productivity levels using Ethiopia as a case study. Topics of discussion include land tenure issues in sub-Saharan Africa, conceptual frame work; and productivity estimates.